2022
DOI: 10.20525/ijrbs.v11i2.1576
|View full text |Cite
|
Sign up to set email alerts
|

Career development for female academics in Australian and South African universities

Abstract: South African and Australian higher education sector is facing challenges of fewer females in leadership positions despite policies in place in both countries. The main purpose of this integrative literature was to analyze and compare journal articles related to career development for female academics in South African and Australian higher education institutions to ascertain the challenges faced by women in both countries. South Africa and Australia were chosen for this study due to the differences in cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It appears that the male domination that prevails in the university field is linked to the under-representation of women faculty members in the administrative field of the university and to their non recruitment to high administrative positions. This reality is often accompanied by phenomena of devaluation, marginalising, biased comments, and professional sexism at the expense of women faculty members (Barrett & Barrett, 2011;Danell & Hjerm, 2013;Fotaki, 2013;Giuffrida, Steffey, Balsa, Morello, & Kapatkin, 2020;Harris, Ravenswood, & Myers, 2013;Hashim, Noman, & Kaur, 2016;Kanyumba & Lourens, 2022;Kele & Pietersen, 2015;McNae & Vali, 2015).…”
Section: The Under-representation Of Women Faculty Members In Adminis...mentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that the male domination that prevails in the university field is linked to the under-representation of women faculty members in the administrative field of the university and to their non recruitment to high administrative positions. This reality is often accompanied by phenomena of devaluation, marginalising, biased comments, and professional sexism at the expense of women faculty members (Barrett & Barrett, 2011;Danell & Hjerm, 2013;Fotaki, 2013;Giuffrida, Steffey, Balsa, Morello, & Kapatkin, 2020;Harris, Ravenswood, & Myers, 2013;Hashim, Noman, & Kaur, 2016;Kanyumba & Lourens, 2022;Kele & Pietersen, 2015;McNae & Vali, 2015).…”
Section: The Under-representation Of Women Faculty Members In Adminis...mentioning
confidence: 99%
“…The literature review study by Kanyumba and Lourens (2022) was concerned with investigating the course of the professional career of women faculty members and their efforts to advance to high administrative positions in the university hierarchy in South Africa and Australia. This study revealed the great and arduous effort women academics must make in these two countries in order to claim administrative positions in the university field.…”
Section: The Under-representation Of Women Faculty Members In Adminis...mentioning
confidence: 99%